2015
DOI: 10.7326/m14-0692
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, Harms, and Cost-Effectiveness of Supplemental Ultrasonography Screening for Women With Dense Breasts

Abstract: Background At least nineteen states have laws that require telling women with dense breasts and a negative screening mammogram to consider supplemental screening. The most readily available supplemental screening modality is ultrasound, yet little is known about its effectiveness. Objective To evaluate the benefits, harms, and cost-effectiveness of supplemental ultrasound screening for women with dense breasts. Design Comparative modeling with 3 validated simulation models. Data Sources Surveillance, Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 40 publications
1
139
0
2
Order By: Relevance
“…An analysis of the cost effectiveness of screening ultrasound for women with dense breasts by Sprague et al [112] measured breast cancer deaths averted, quality-adjusted life years gained (QALY), false positives, costs, and costs per QALY gained. When reviewing the age group of 50–74, supplemental screening ultrasound averted 0.36 additional breast cancer deaths; gained 1.7 QALYs, and resulted in 354 false-positive biopsy recommendations.…”
Section: The Current Clinical Landscape Of Mbdmentioning
confidence: 99%
“…An analysis of the cost effectiveness of screening ultrasound for women with dense breasts by Sprague et al [112] measured breast cancer deaths averted, quality-adjusted life years gained (QALY), false positives, costs, and costs per QALY gained. When reviewing the age group of 50–74, supplemental screening ultrasound averted 0.36 additional breast cancer deaths; gained 1.7 QALYs, and resulted in 354 false-positive biopsy recommendations.…”
Section: The Current Clinical Landscape Of Mbdmentioning
confidence: 99%
“…37 In a comparative modeling study, researchers found that adding ultrasound averted 0.36 additional breast cancer deaths but resulted in 354 unnecessary benign biopsies per 1,000 women screened. 37 Even though the comparative weighting of relatively rare benefits of deaths prevented and more common risks such as benign biopsies is somewhat subjective, researchers concluded that adding ultrasound to digital mammography screening likely causes more harm relative to benefits gained.…”
Section: Potential Supplemental Screening Modalities For Women With Dmentioning
confidence: 99%
“…Certain published analyses that aimed to identify subgroups for whom screening before age 50 was beneficial suggest that women with extremely dense breasts may benefit from beginning screening in their forties (13) and by choosing an annual rather than biennial interval (14). No direct evidence supports use of supplemental ultrasound or MRI in the general population of women with dense breasts, although modeling studies suggest that supplemental ultrasound following a negative mammogram may increase cancer detection but at the cost of substantially increased false-positive rates (15). Over 90 genetic susceptibility loci have been identified (7), but common genetic variants or polygenic risk scores are yet to be incorporated into screening recommendations; statistical modeling suggests, though, that they could decrease the number needed to screen while preserving the ability to identify most currently screen-detectable cancers (9).…”
Section: Challenges and Opportunities For Precision Medicine Screeninmentioning
confidence: 99%